Red Light‐Emitting Thermally‐Activated Delayed Fluorescence of Naphthalimide‐Phenoxazine Electron Donor‐Acceptor Dyad: Time‐Resolved Optical and Magnetic Spectroscopic Studies. Issue 37 (23rd May 2022) - Zhang, Xue; Liu, Xiao; Taddei, Maria; Bussotti, Laura; Kurganskii, Ivan; Li, Minjie; Jiang, Xiao; Xing, Longjiang; Ji, Shaomin; Huo, Yanping; Zhao, Jianzhang; Di Donato, Mariangela; et al.
Abstract: We prepared an orthogonal compact electron‐donor (phenoxazine, PXZ)‐acceptor (naphthalimide, NI) dyad (NI‐PXZ ), to study the photophysics of the thermally‐activated delayed fluorescence (TADF), which has a luminescence lifetime of 16.4 ns (99.2 %)/17.0 μs (0.80 %). A weak charge transfer (CT) absorption band was observed for the dyad, indicating non‐negligible electronic coupling between the donor and acceptor at the ground state. Femtosecond transient absorption spectroscopy shows a fast charge separation (CS) (ca. 2.02∼2.72 ps), the majority of the singlet CS state is short‐lived, especially in polar solvents ( τ CR = 10.3 ps in acetonitrile, vs. 1.83 ns in toluene, 7.81 ns in n ‐hexane). Nanosecond transient absorption spectroscopy detects a long‐lived transient species in n ‐hexane, which is with a mixed triplet local excited state ( 3 LE) and charge separated state ( 3 CS), the lifetime is 15.4 μs. In polar solvents, such as tetrahydrofuran and acetonitrile, a neat 3 CS state was observed, whose lifetimes are 226 ns and 142 ns, respectively. Time‐resolved electron paramagnetic resonance (TREPR) spectra indicate the existence of strongly spin exchanged 3 LE/ 3 CT states, with the effective zero field splitting (ZFS) | D | and | E | parameters of 1484 MHz and 109 MHz, respectively, much smaller than that of the native 3 NI state (2475 and 135 MHz). It is rare but solid experimental evidence that a closely‐lying 3 LE state is crucial for occurrence of TADF and this 3 LE state is an essential intermediate state to facilitate reverse intersystem crossing in TADF systems. Abstract : The locally‐excited triplet state ( 3 LE) is found as an essential intermediate state in thermally activated delayed fluorescence (TADF) of compact electron‐donor‐acceptor system. 3 LE and charge‐separated states ( 1 CS and 3 CS) are close to each other in energy, the interaction of three states causes TADF, which is analyzed by femtosecond/nanosecond transient absorption spectra and time‐resolved electron paramagnetic resonance spectroscopy.